Analisis Pengaruh Supply dan Demand Valas dengan Variabel Makroekonomi terhadap Pergerakan Nilai Tukar Rupiah di Indonesia Tahun 2001-2018 - Putri, Mayshara Nanda; Widayatsari, Any; Aulia, Ando Fahda (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2019)
This research aims to analyze the effect of foreign exchange supply and demand activities using macroeconomic variables of inflation, foreign direct investment and external debt on movement of rupiah exchange rate. The method used is descriptive quantitative and analyzed simultaneously and partially with OLS (ordinary least square) multiple linear regression. The result shows that simultaneously, inflation, foreign direct investment, and external debt has a significant effect on rupiah exchange rate. Meanwhile, partially, inflation and external debt has a significant positive effect on rupiah exchange rate, however foreign direct investment has a significant negative effect on rupiah exchange rate.